Community Ecology and Conservation of Bear-Salmon Ecosystems - Levi, Taal; Hilderbrand, Grant V.; Hocking, Morgan D.; Quinn, Thomas P.; White, Kevin S.; Adams, Megan S.; Armstrong, Jonathan B.; Crupi, Anthony P.; Darimont, Christopher T.; Deacy, William; Gilbert, Sophie L.; Ripple, William J.; et al. (Frontiers in Ecology and Evolution, 2020)
Apex predators play keystone roles in ecosystems through top-down control, but the effects of apex omnivores on ecosystems could be more varied because changes in the resource base alter their densities and reverberate through ecosystems in complex ways. In coastal temperate ecosystems throughout much of the Northern Hemisphere, anadromous salmon once supported abundant bear populations, but both taxa have declined or been extirpated from large parts of their former ranges with limited research on the consequences of diminished or absent interactions among species. Here we review the biogeography of bear-salmon interactions and the role of salmon-subsidized bears in (1) resource provisioning to plants and scavengers through the distribution of salmon carcasses, (2) competition among bears and other large carnivores, (3) predation of ungulate neonates, (4) seed dispersal, and (5) resource subsidies to rodents with seed-filled scats. In addition to our review of the literature, we present original data to demonstrate two community-level patterns that are currently unexplained. First, deer densities appear to be consistently higher on islands with abundant brown bears than adjacent islands with black bears and wolves, and moose calf survival is higher at low bear densities (<~25 bears per 100 km2) but is constant across the vast majority of bear densities found in the wild (i.e., ~>25 bears per 100 km2). Our review and empirical data highlight key knowledge gaps and research opportunities to understand the complex ecosystem effects related to bear-salmon interactions.